Dopamine transporter site-directed mutations differentially alter substrate transport and cocaine binding. - Kitayama, S (1992)
Polar amino acids lying within three hydrophobic regions of the dopamine transporter (DAT) are analogous to those important for ligand recognition by catecholamine receptors. Possible functional significance of these amino acids was examined by expressing DAT cDNAs mutated in these polar residues. Replacement of aspartate at position 79 with alanine, glycine, or glutamate dramatically reduced uptake of [3H]dopamine and the tritium-labeled Parkinsonism-inducing neurotoxin 1-methyl-4-phenylpyridinium (MPP+) and reduced the mutants' affinity for the tritium-labeled cocaine analog (-)-2 beta-carbomethoxy-3 beta-(4-fluorophenyl)tropane (CFT) without affecting Bmax. Replacement of the serine residues at positions 356 and 359 in the seventh hydrophobic region by alanine or glycine caused reductions in [3H]dopamine and [3H]MPP+ uptake, whereas [3H]CFT binding was less affected. Substitution of two serines in the eighth hydrophobic region yielded wild-type values for [3H]dopamine and [3H]MPP+ uptake and [3H]CFT binding. These results demonstrate that aspartate and serine residues lying within the first and seventh hydrophobic putative transmembrane regions are crucial for DAT function and provide identification of residues differentially important for cocaine binding and for dopamine uptake.